Analisis Tingkat Kepuasan Nasabah Terhadap Pelayanan PT. BPR Segara Anak Kencana Aikmel Lombok Timur - Andhas Pebriani Karyadi; Junaidi Sagir; Handri Amien Effendi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2020)
The purpose of this research is to analyze and know the level of customer satisfaction and also to know the elements of service performance must be improved again by the PT. BPR Segara Anak Kencana Aikmel. This study uses the five dimensions of service quality with a variable number of sub-15 sub-variables. Type of research used in this research is descriptive research with a sample survey method. Population used in this study is the customer of PT. BPR Segara Anak Kencana Aikmel in 2008 which amounted to 5307 people while the determination of the number of respondents is determined by the formula slovin, taking respondents used Accidental sampling techniques. This study uses a sample of 100 respondents. Method of data collection using questionnaires, and as a tool of data analysis, the author uses the Consumer Satisfaction Index and a Cartesian diagram. From the results of data analysis writer get 2 important result are: Quality of service at PT. BPR Segara Anak Kencana Aikmel based overall GPA in accordance with the customer response is expressed very well or very satisfactory. And based on the description of a Cartesian diagram, it can be concluded that the essential elements that should be raised again the performance elements of the existing services in Quadrant A, because in this quadrant are service elements that have not been implemented well by the PT. BPR Segara Anak Kencana Aikmel